Older men display elevated levels of senescence‐associated exercise‐responsive CD28null angiogenic T cells compared with younger men. Issue 12 (25th June 2018) - Ross, Mark; Ingram, Lesley; Taylor, Guy; Malone, Eva; Simpson, Richard J.; West, Dan; Florida‐James, Geraint
Abstract: Aging is associated with elevated cardiovascular disease risk. As a result of aging, endothelial dysfunction develops, partly due to a reduction in vascular regenerative ability. CD31 + T cells (angiogenic T cells; TANG ) possess highly angiogenic capabilities; however, these cells are significantly reduced in older populations. In addition, older populations possess significantly higher senescent and highly differentiated T‐cell levels in circulation, and these are reported to be highly exercise responsive. We investigated whether older adults display greater levels of circulating senescent (CD28 null ) TANG cells and whether these cells were more exercise responsive than CD28 + TANG cells. Young (18–25 years; n  = 9) and older (60–75 years; n  = 10) healthy men undertook a 30‐min cycling bout at 70% V ˙ O2 peak, with circulating TANG cells (CD3 +  CD31 +  CD28 +/null ; including CD4 + and CD8 + subsets) measured preexercise, postexercise, and 1 h post exercise by flow cytometry. Older adults displayed reduced basal levels of TANG cells (mean ± SEM: 410 ± 81 vs. 784 ± 118 cells· μ L, P  = 0.017), despite a greater proportion of these cells being CD28 null (26.26 ± 5.08 vs. 13.36 ± 2.62%, P  = 0.044). Exercise significantly increased the circulating number of TANG cells in both young and older men. However, in older men alone, exercise preferentially mobilized CD28 null CD8 + TANG cells compared with CD28 + TANG cells (time × phenotype interaction: P  = 0.022; Δ74 ± 29 vs. Δ27 ± 15 cells· μ L, P  = 0.059), with no such difference observed between these phenotypes in the young population. In conclusion, this is the first study to demonstrate that despite observing lower circulating numbers of TANG cells, older adults display greater levels of senescent TANG cells in comparison with younger individuals, and these cells are more exercise responsive than CD28 + TANG cells. Lower number of circulating TANG and greater levels of senescent‐associated CD28 null TANG may contribute to greater CVD risk with advancing age. Abstract : Senescent angiogenic T cells were quantified in circulation of young and older healthy men, at rest and after an acute bout of exercise. Older adults displayed greater levels of senescent angiogenic T cells which displayed greater responsiveness to exercise than naïve angiogenic T cells in this older population.